Negotiating Malay identities in Singapore : the role of modern Islam - Rizwana Abdul Azeez (Brighton ; Chicago : Sussex Academic Press, 2016)
"Singapore Malays subscribe to mostly traditional rather than modern interpretations of Islam. Singapore state officials, however, wish to curb the challenges such interpretations bring to the country's political, social, educational and economic domains. Thus, these officials launched a programme to socially engineer modern Muslim identities amongst Singapore Malays in 2003, which is ongoing. Negotiating Malay Identities in Singapore documents a variety of ethnographic encounters that point to the power struggles surrounding two basic and very different ways of living. While the Singapore state has gained some successes for its project, it has also faced significant and multiple setbacks. Amongst them, state officials have had to contend with traditional Islamic authority that Malay elders carry and who cannot be ignored because these elders are time-entrenched figures of repute in their community. One of the book's significant contributions is that it documents how Singapore, an avowedly secular state, has now turned to Islam as a tool for governance. Just as significant are the insights the study provides on another aspect of Singapore state governance, one usually described as 'authoritarian'. The book demonstrates that even authoritarian states can face serious obstacles in the face of religion's influence over its followers. Moreover, the academic literature on Singapore Malays is sparse and this work not only fills gaps in the existing literature but provides new and original research data"--
A prologue: the Singapore State, power talk and Malays -- Modernising Singapore Malays -- The state's gaze on Malays -- The State and its management of religion -- Implementing modernity: omissions and ambivalences -- The administration of Muslim law act and MUIS: bureaucratised places and personal spaces -- Time: logically coherent versus socially coherent approaches -- Jawi, Romanised Malay and English: dialectical co-existences -- Conclusion -- Appendix A: The Singapore Muslim Identity (SMI) project -- Appendix B: -- The chain of authority (Ijazah) of Umar bin Abd al-Rahman.
Includes bibliographical references and index.
Keywords: Muslims -- Singapore; Islam and state -- Singapore; Malays (Asian people) -- Singapore -- Social conditions; Singapore; Australian